Effect of glycine supplementation on sulfur amino acid use in growing cattle - Lambert, B.D.; Löest, C.A.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Previous research has suggested the possibility that the supply of glycine, a nonessential amino acid, might affect how efficiently cattle use methionine. This study was conducted to determine the role of glycine on methionine utilization in growing steers as well as how glycine might impact utilization of cysteine, an amino acid produced in the body from methionine. In Exp. 1, treatments were abomasal infusion of 2 or 5 g/day L-methionine and 0 or 50 g/day glycine in a factorial arrangement. Efficiency of methionine use was 27% in the absence of supplemental glycine, but 66% in its presence. Glycine supplementation by itself had little effect on protein deposition. In Exp. 2, treatments were abomasal infusions of 0 or 2.4 g/day L-cysteine and 0 or 40 g/day glycine in a factorial arrangement. Supplementation with cysteine in the absence of supplemental glycine did not change nitrogen balance. In fact, when glycine was supplemented alone, nitrogen retention decreased. However, when glycine and cysteine were supplemented together, nitrogen retention was increased. Thus, in the presence of supplemental glycine, it appears that cysteine can improve protein deposition, presumably by sparing methionine. Comparison of this and earlier studies suggests that B-vitamin status may play an important role in this response.
Keywords: Beef; Glycine; Methionine; Growth